Peripheral cemento-ossifying fibroma of maxilla - Chatterjee Anirban; Ajmera Neha; Singh Amit (Wolters Kluwer Medknow Publications, 2010)
Peripheral cemento-ossifying fibroma is a reactive gingival overgrowth occurring frequently in anterior maxilla. It is a slow-growing benign tumor which may lead to pathologic migration and other periodontal problems, so it should be excised as soon as possible. The recurrence rate of peripheral cemento-ossifying fibroma is reported to be 8% to 20%, so a close postoperative follow-up is required. Herein, we are reporting a similar case of peripheral cemento-ossifying fibroma in the maxillary anterior region.